2020
DOI: 10.4103/ajns.ajns_147_20
|View full text |Cite
|
Sign up to set email alerts
|

An anterior dislocation after Mobi-C cervical disc arthroplasty

Abstract: The objective is to report a case of an early dislocation of Mobi-C prosthesis used for the replacement of C4–C5 disc. A 57-year-old man who was operated 17 years before for C6–C7 fusion complained of cervicalgia associated with bilateral but predominantly right-sided brachialgia. Magnetic resonance imaging demonstrated central and foraminal stenosis in the C5–C6 segment and soft medial disc herniation in the C4–C5 segment. The patient was indicated for the placement of a cervical disc prosthesis C4–C5 and a C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…to aid in fixation. 20,[28][29][30] It seems that the stability of implants is not only related to the anchoring of the implant, so we performed a logistic regression analysis with a larger population and discovered that preoperative kyphosis is significantly associated with postoperative implant dislocation. It is worth mentioning that patients with kyphosis are not good candidates for CDA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…to aid in fixation. 20,[28][29][30] It seems that the stability of implants is not only related to the anchoring of the implant, so we performed a logistic regression analysis with a larger population and discovered that preoperative kyphosis is significantly associated with postoperative implant dislocation. It is worth mentioning that patients with kyphosis are not good candidates for CDA.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of implant dislocation has been inconsistent, according to previous reports. 4,[20][21][22][23][24][25][26][27][28][29][30] Moreover, reports have warned that implant dislocation could occur beyond 3 to 6 months postoperatively. 27 However, we found that most migrations can be seen on plain radiographs at the early postoperative visit, which is about 0.9 to 1.4 months postoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CDA decreases the risks of certain potential adverse events of ACDF, such as pseudarthrosis 16 . However, as with all surgical procedures, they also have their own unique set of adverse events due to their motion preservation mechanics, including heterotopic ossification, osteolysis, and dislocation 17–20 …”
Section: What We Knowmentioning
confidence: 99%
“…16 However, as with all surgical procedures, they also have their own unique set of adverse events due to their motion preservation mechanics, including heterotopic ossification, osteolysis, and dislocation. [17][18][19][20]…”
mentioning
confidence: 99%